The Antitumor Activities of Marsdenia tenacissima - Wang, Xiang; Yan, Yuanliang; Chen, Xi; Zeng, Shuangshuang; Qian, Long; Ren, Xinxin; Wei, Jie; Yang, Xue; Zhou, Yangying; Gong, Zhicheng; Xu, Zhijie (Frontiers in Oncology, 2018)
Marsdenia tenacissima (MT), a traditional Chinese herbal medicine, has long been used for thousands of years to treat asthma, tracheitis, rheumatism, etc. An increasing number of recent studies have focused on the antitumor effects of MT. The effects of MT on cancer are the result of various activated signaling pathways and inhibiting factors and the high expression levels of regulatory proteins. MT can inhibit different cancer types including non-small cell lung cancer (NSCLC), malignant tumors, hepatic carcinoma and so on. This article mainly focuses on the activities and mechanisms of MT. In addition, the efficacy and toxicity of MT are also discussed. Further studies of MT are required for improved medicinal utilization.